Maximizing Utility And Distributing Income Equitably: How does Zakah Impact Both of Them at Once? - Ade Nur Rohim (Islamic Economics Journal, 2018)
This paper is a theoretical article that examines how zakah is able to fulfill and increase the satisfaction of a Muslim consumer, even if it reduces the quantity of goods consumed. In addition, this article will also clarify the role and function of zakah in dealing with the problem of economic inequality. Economic inequality is characterized by uneven distribution of income and wealth and only revolves around a handful of people. This made the gap between rich and poor deepening. One of the factors causing the gap is the behavior of consumers who tend to pursue pure utility. So that it fosters greed in itself and increases negative behaviors such as hoarding property, and makes wealth not circulated in the community evenly. This study also identifies the impact of zakat on public consumption behavior which also has direct implications for income distribution. The results of the study show that utility in Islamic economics is a combination of two utilities. Worldly utilities that represent real satisfaction directly felt such as feeling full, happiness in the world, fulfilled their life needs. Also the ukhrawi utility is represented by an increase in faith and piety, and a reward that is expected to be obtained in the hereafter. Where zakah is able to increase the two types of utilities. This concept encourages rich Muslim communities to distribute their income through zakat instruments to the poor. So that the redistribution of income fairly can be realized through zakah, and in the end is able to realize equitable welfare in the community.